Neue-Gemeinschaft: Transformasi Digital pada Usaha Mikro, Kecil dan Menengah di Komunitas Pedesaan Banyuwangi, Jawa Timur - Mazya, Thita; M Kolopaking, Lala; Hadi Dharmawan, Arya; Ridho Nurrochmat, Dodik; Satria, Arif (Sodality: Jurnal Sosiologi Pedesaan, 2022)
This study aims to analyze the digital transformation of changing rural economy towards a digital society. Qualitative research methods were used, including 50 participants and in-depth interview informants, with participatory observation, policy analysis, and three series of focus group discussions both in person and online. The study found that internet intervention significantly impacts collective behaviour and improves MSMEs development. Referring to the continuum theory of Gemeinschaft-Gesellschaft, the study showed that these changes result in the formation of a ‘Neue Gemeinschaft’. Rural MSMEs are entering a new era due to the adoption of digital technology by businesses that support and exhibit characteristics such as the intensity of the use of internet networks, the ability to conduct digital transactions, and the preservation of village social values. Theoretically and empirically, the research indicates that digital transformation is driven by a change in collective behaviour around technology use, followed by inclusive rural digital economy.